Experiences on the implementation and maintenance of the Canadian Disability Participation Project: A mixed-methods study - Femke Hoekstra; Alanna Shwed; Sarah Lawrason; Kathleen A. Martin Ginis; Veronica Allan; Anita Kothari; Christopher B. McBride; Heather L. Gainforth (PLoS ONE, 2025)
Establishing a multidisciplinary network of researchers, trainees, and research users—such as the Canadian Disability Participation Project (CDPP)—is a promising approach to promote and support research partnerships and improve the application of disability research findings. This study aimed to 1) describe the implementation of the CDPP network over time and 2) explore members’ experiences and reflections on the implementation and maintenance of the CDPP network and its partnerships. This mixed-methods study used survey data, collected among CDPP researchers, trainees and research users in the years 2018, 2019 and 2021, and interview data, collected at the end of the study period (2021/2022). Survey items, focused on network functioning and satisfaction (implementation), were analyzed using descriptive statistics. Interviews focused on members’ experiences and reflections of the implementation and maintenance of the network and its partnerships, and were analyzed using reflexive thematic analysis. Members were positive about how the network functioned and satisfied with how the CDPP implemented its plans. Over 70% of the survey participants indicated that it was easy to work with researchers/research users in the CDPP network (2018: 71%; 2019: 85%; 2021: 70%). Interview participants discussed the strong leadership of the network, the lack of feeling meaningfully connected to the network as a whole, and key principles that guide the success of individual research partnerships (implementation). Participants reported that (human) resources and continued leadership are needed to sustain the network and its partnerships long-term (maintenance). This study provides unique longitudinal insights into the implementation of a multidisciplinary network of research partnerships. The findings highlighted that building and sustaining a large network of partnerships is challenging and requires strong and continued leadership. To conclude, we describe lessons learned for research partnership capacity building and the translation of disability research to practice and policy.